Bioequivalence Study of Warfarin in Healthy Chinese Volunteers With a Validated High‐Performance Liquid Chromatography‐Mass Spectrometry Method. Issue 3 (3rd April 2017) - Li, Wenlong; Bu, Fanlong; Li, Rong; Wang, Benjie; Shaikh, Abdul Sami; Zhang, Yunyun; Guo, Ruichen; Zhang, Rui
Abstract: This study was designed to investigate the pharmacokinetics of an innovative film‐coated warfarin sodium tablet and to compare it with the marketed sugar‐coated warfarin sodium tablet in humans. A single‐dose, open‐label, randomized, two‐way crossover study was performed in 24 healthy Chinese male volunteers. They were administered 2.5 mg of innovative film‐coated warfarin sodium tablets or the marketed sugar‐coated warfarin sodium tablets. Blood samples were collected at different time points after dosing for investigation of the pharmacokinetics of warfarin in human plasma. A sensitive liquid chromatography mass spectrometry method was established to determine warfarin in plasma. Drug and Statistics 2.1.1 was applied to calculate the pharmacokinetics parameters. The main pharmacokinetic parameters for film‐coated and sugar‐coated warfarin were the following: t½, 103.5 ± 18.8 and 105.8 ± 21.3 hours; Tmax, 0.7 ± 0.5 and 1.3 ± 0.8 hours; Cmax, 347.8 ± 74.8 and 322.9 ± 75.7 ng/mL; AUC0∼360, 16, 024.2 ± 3713.9 and 15, 586.6 ± 3477.0 ng·mL −1 ·h; AUC0∼∞, 17, 335.7 ± 4089.1 and 16, 912.0 ± 3911.2 ng·mL −1 ·h, respectively. The human pharmacokinetics of film‐coated and sugar‐coated warfarin were slightly different. The oral absorption and bioavailability of innovative film‐coated warfarin were slightly higher than those of the sugar‐coated warfarin. This study is vital to clinical usage of warfarin not only because of the pharmacokinetic parameters of the 2 pharmaceutical dosage forms of warfarin but also to obtain data on the prevalence of CYP2C9 and VKORC1 genes and their influence on the concentration of warfarin.